Unlocking the Potential of Exosomes: Transforming Wound Healing and Therapeutic Potential - Shahjad; Fatma, Nishat; Ali, Zeeshan; Kumar, Arun; Moonis, Mohd; Chandra, Phool (MicroRNA, 2025)
Difficulties in wound healing pose a considerable clinical problem and are a significant source of morbidity in the general population. Systemic disorders such as diabetes and venous insufficiency often result in chronic wounds and an impaired healing process. The healthcare cost of treating chronic wounds in the U.S. already exceeds 20 billion dollars per year and is expected to rise with an aging population and increasing incidence of diabetes. Recently, research and review articles have been used to understand the normal healing process and identify the reasons why certain wounds fail to heal, which should enable the development of more effective therapeutic interventions. Animal models have provided valuable information; however, the healing process differs between humans and animals, and data obtained from in vitro studies can be challenging to extrapolate to a clinical context. In conclusion, this study aims to summarize the current understanding of inflammation, epithelialization, and tissue repair processes, mainly through the use of data from <span class=
Keywords: Wound healing